An Evaluation of the CHIMERE Chemistry Transport Model to Simulate Dust Outbreaks across the Northern Hemisphere in March 2014 - Bertrand Bessagnet; Laurent Menut; Augustin Colette; Florian Couvidat; Mo Dan; Sylvain Mailler; Laurent Létinois; Véronique Pont; Laurence Rouïl (Atmosphere, 2017)
Mineral dust is one of the most important aerosols over the world, affecting health and climate. These mineral particles are mainly emitted over arid areas but may be long-range transported, impacting the local budget of air quality in urban areas. While models were extensively used to study a single specific event, or make a global analysis at coarse resolution, the goal of our study is to simultaneously focus on several affected areas—Europe, North America, Central Asia, east China and the Caribbean area—for a one-month period, March 2014, avoiding any parameter fitting to better simulate a single dust outbreak. The simulation is performed for the first time with the hemispheric version of the CHIMERE model, with a high horizontal resolution (about 10 km). In this study, an overview of several simultaneous dust outbreaks over the Northern Hemisphere is proposed to assess the capability of such modeling tools to predict dust pollution events. A quantitative and qualitative evaluation of the most striking episodes is presented with comparisons to satellite data, ground based particulate matter and calcium measurements. Despite some overestimation of dust concentrations far from emission source areas, the model can simulate the timing of the arrival of dust outbreaks on observational sites. For instance, several spectacular dust storms in the US and China are rather well captured by the models. The high resolution provides a better description and understanding of the orographic effects and the long-range transport of dust plumes.